2010
DOI: 10.1007/s11192-010-0184-x
|View full text |Cite
|
Sign up to set email alerts
|

A citation analysis of Iranian journals to open access (OA) articles and journals

Abstract: This study was survey on citation research of Open Access (OA) journals in English papers of Iranian universities journals during year 2007. The main purposes of this paper were: to examine the state of English papers in Iranian journals in Thomson Scientific Master Journal List (TSMJL); and to analyze their visibility through citations to OA journals in DOAJ database. In fact, the researcher has used of citation analysis technique of bibliometric and large-scale sociometric analyses on about 16,219 citations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Harirchi and co-workers (2007) have studied the reasons of co-authorship between Iranian and other countries scientists in the fields of physics, chemistry, and biology. Asemi (2010) has studied the proportion of citations to open access journals, which showed a huge difference in compare with citation to other journals. Recently, Sotudeh (2010) has studied the impact of Iranian scientific publications on the global science of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Harirchi and co-workers (2007) have studied the reasons of co-authorship between Iranian and other countries scientists in the fields of physics, chemistry, and biology. Asemi (2010) has studied the proportion of citations to open access journals, which showed a huge difference in compare with citation to other journals. Recently, Sotudeh (2010) has studied the impact of Iranian scientific publications on the global science of the world.…”
Section: Introductionmentioning
confidence: 99%
“…During the last few decades, OA journal impact has been measured mainly by studying the coverage in databases or citation indices available in citation databases, such as total cites, IF (impact factor), immediacy index (Koehler et al , 2000; Hawkins, 2001; Sotudeh and Horri, 2007; Lin, 2009; Aragudige and Kevin, 2009; Asemi, 2010). In 2004, ISI reported that traditional journals and OA journals had similar IFs (McVeigh, 2004; Pringle, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%